The Arabidopsis TAC Position Viewer: a high‐resolution map of transformation‐competent artificial chromosome (TAC) clones aligned with the Arabidopsis thaliana Columbia‐0 genome. (September 2015) - Hirose, Yoshitsugu; Suda, Kunihiro; Liu, Yao‐Guang; Sato, Shusei; Nakamura, Yukino; Yokoyama, Koji; Yamamoto, Naoki; Hanano, Shigeru; Takita, Eiji; Sakurai, Nozomu; Suzuki, Hideyuki; Nakamura, Yasukazu; et al.
Summary We present a high‐resolution map of genomic transformation‐competent artificial chromosome (TAC) clones extending over all Arabidopsis thaliana (Arabidopsis) chromosomes. The Arabidopsis genomic TAC clones have been valuable genetic tools. Previously, we constructed an Arabidopsis genomic TAC library consisting of more than 10 000 TAC clones harboring large genomic DNA fragments extending over the whole Arabidopsis genome. Here, we determined 13 577 end sequences from 6987 Arabidopsis TAC clones and mapped 5937 TAC clones to precise locations, covering approximately 90% of the Arabidopsis chromosomes. We present the large‐scale data set of TAC clones with high‐resolution mapping information as a Java application tool, the Arabidopsis TAC Position Viewer, which provides ready‐to‐go transformable genomic DNA clones corresponding to certain loci on Arabidopsis chromosomes. The TAC clone resources will accelerate genomic DNA cloning, positional walking, complementation of mutants and DNA transformation for heterologous gene expression.